Do Justice, Love Kindness, and Walk Humbly with God as A Form of True Worship: A Reading of Micah 6:8 - Isakh Hendrik; Ira Desiawanti Mangililo (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2023)
Abstract: Abstract: This paper examines the meaning of true worship according to Micah 6:8. A socio-historical analysis and linguistic criticism of Micah 6:8 highlights the three important elements needed to gain access to God namely â€œto do justice, to love kindness, and to walk humbly with God.â€ Hence, Micah 6:8 functions a warning that our religious ritual life must go hand in hand with our ethical responsibilities. The church as a community needs to be grounded in this theological foundation and embrace the understanding that true worship is not only celebrated through our vertical relationship with God, but also manifested through horizontal relationships with others. We can do this by reaching out to those who are economically, socially, culturally, and politically vulnerable; and live in harmony and peace within the community and with all of creationÂ Keywords: justice, love kindness, ritual, solidarity, worship